PENGARUH STRUKTUR MODAL, PERPUTARAN MODAL KERJA, KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERATIG PADA PERUSAHAAN INFRASTRUKTUR YANG TERDAFTAR DIBURSA EFEK INDONESIA PERIODE 2015-2018 - Haogonasokhi Telaumbanua; Vica Anisa Simanjuntak; Mastika Marbun; Elisa Agustina Br Sembiring; Deasy Arisandy Aruan (Faculty of Economics and Business, Universitas Warmadewa, 2021)
This study has the objective, namely to know whether the capital structure, working capital turnover, and dividend policy affect the value of the company, and whether profitability can strengthen or weaken the influence of capital structure, working capital turnover and dividend policy on firm value. The population of 71 companies and 44 samples after multiplied by 4 years using the purposive sampling method and data analysis method with the results of the financial statements of infrastructure and utility companies on the Indonesia Stock Exchange for the period 2015-2018. This study states that partially the capital structure has a positive and significant effect on firm value, while working capital turnover, dividend policy has no influence and is not significant on firm value. Simultaneously, variable capital structure, working capital turnover, and dividend policy have no influence and are not significant on firm value. And the profitability variable weakens the influence of capital structure, working capital turnover, and dividend policy on firm value because the significance value is below 0.05.